Adaptive Skeletal Muscle Action Requires Anticipation and “Conscious Broadcasting” - Poehlman, T. Andrew; Jantz, Tiffany K.; Morsella, Ezequiel (Frontiers in Psychology, 2012)
Historically, the conscious and anticipatory processes involved in voluntary action have been associated with the loftiest heights of nervous function. Concepts like mental time travel, ‘theory of mind,’ and the formation of the ‘self’ have been at the center of many attempts to determine the purpose of consciousness. Eventually, more reductionistic accounts of consciousness emerged, proposing rather that conscious states play a much more basic role in nervous function. Though the widely held ‘integration consensus’ proposes that conscious states integrate information-processing structures and events that would otherwise be independent, Supramodular Interaction Theory (SIT) argues that conscious states are necessary for the integration of only certain kinds of information. As revealed in this selective review, this integration is related to what is casually referred to as ‘voluntary’ action, which is intimately related to the skeletal muscle output system. Through a peculiar form of broadcasting, conscious integration often controls and guides action via ‘ideomotor’ mechanisms, where anticipatory processes play a central role. Our selective review covers evidence (including findings from anesthesia research) for the integration consensus, SIT, and ideomotor theory.